2008
DOI: 10.1111/j.1745-6916.2008.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

In Pursuit of Happiness: Empirical Answers to Philosophical Questions

Abstract: In this article, we provide an overview of what various philosophers throughout the ages have claimed about the nature of happiness, and we discuss to what extent psychological science has been able to substantiate or refute their claims. We first address concerns raised by philosophers regarding the possibility, desirability, and justifiability of happiness and then turn to the perennial question of how to be happy. Integrating insights from great thinkers of the past with empirical findings from modern behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
0
16

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(107 citation statements)
references
References 51 publications
2
89
0
16
Order By: Relevance
“…The top of the ladder represents the best possible life for you and the bottom of the ladder represents the worst possible life for you. The Cantril Ladder is hedonic (following the thinking of Bentham) as opposed to eudaimonic (in line with the thinking of Aristotle) (Kesebir and Diener, 2008;Nordbakke and Schwanen, 2014;Ryff and Singer, 2008), in that it assumes that the subject is the best judge of what makes her happy, as opposed to comparing subject's life to an externally devised set of values (see Banister and Bowling, 2004;De Vos et al, 2013;Nordbakke and Schwanen, 2014;Ryff and Singer, 2008). The hedonic and eudaimonic approaches differ, but each has value and is worth pursuing (Delbosc, 2012).…”
Section: Life Satisfaction (L)mentioning
confidence: 95%
See 1 more Smart Citation
“…The top of the ladder represents the best possible life for you and the bottom of the ladder represents the worst possible life for you. The Cantril Ladder is hedonic (following the thinking of Bentham) as opposed to eudaimonic (in line with the thinking of Aristotle) (Kesebir and Diener, 2008;Nordbakke and Schwanen, 2014;Ryff and Singer, 2008), in that it assumes that the subject is the best judge of what makes her happy, as opposed to comparing subject's life to an externally devised set of values (see Banister and Bowling, 2004;De Vos et al, 2013;Nordbakke and Schwanen, 2014;Ryff and Singer, 2008). The hedonic and eudaimonic approaches differ, but each has value and is worth pursuing (Delbosc, 2012).…”
Section: Life Satisfaction (L)mentioning
confidence: 95%
“…For thousands of years, philosophers have asked what brings us happiness (Kesebir and Diener, 2008). Today, however, thanks to modern data gathering, statistical techniques, and computing power, we are finally uncovering empirical answers to this question.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, happiness went from being related to luck and considered as being passive to being considered a more active construct. Currently, happiness is understood as something that humans beings can control and achieve (Kesebir and Diener, 2008; Oishi, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…For example, research on how people deal with antisocial behavior shows that punishing violators is experienced as pleasurable even when it costs in terms of one's material standing (Angier 2002). The vast body of research on human well-being has identified many dimensions of this complex domain, including hedonic pleasure, emotional well-being, psychological capital, and character strengths (e.g., Ring et al 2007;Kesebir & Diener 2008;Ryff & Singer 2008). Particularly pertinent to the discussion here is that many human qualities are inconsistently exhibited within the same person across time and circumstances.…”
mentioning
confidence: 99%